2016
DOI: 10.1167/16.9.4
|View full text |Cite
|
Sign up to set email alerts
|

The perception of ego-motion change in environments with varying depth: Interaction of stereo and optic flow

Abstract: When estimating ego-motion in environments (e.g., tunnels, streets) with varying depth, human subjects confuse ego-acceleration with environment narrowing and ego-deceleration with environment widening. Festl, Recktenwald, Yuan, and Mallot (2012) demonstrated that in nonstereoscopic viewing conditions, this happens despite the fact that retinal measurements of acceleration rate-a variable related to tau-dot-should allow veridical perception. Here we address the question of whether additional depth cues (specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
2
3
0
Order By: Relevance
“…This finding partially supports the recent notion that stereoscopic information can contribute to vection in multiple ways (Allison et al, 2014;Palmisano et al, 2016). On the other hand, Ott, Pohl, Halfmann, Hardiess, and Mallot (2016) reported that stereoscopic information about spatial layout of the environments did not disambiguate the confusion between the narrowing (or widening) environments and self-motion acceleration (or deceleration), suggesting that earlier visual processing for self-motion might ignore both parallactic and stereoscopic information about the spatial layout of the environments. However, their findings also leave open the possibility of cue combination at a later stage of visual processing.…”
Section: Discussionsupporting
confidence: 84%
“…This finding partially supports the recent notion that stereoscopic information can contribute to vection in multiple ways (Allison et al, 2014;Palmisano et al, 2016). On the other hand, Ott, Pohl, Halfmann, Hardiess, and Mallot (2016) reported that stereoscopic information about spatial layout of the environments did not disambiguate the confusion between the narrowing (or widening) environments and self-motion acceleration (or deceleration), suggesting that earlier visual processing for self-motion might ignore both parallactic and stereoscopic information about the spatial layout of the environments. However, their findings also leave open the possibility of cue combination at a later stage of visual processing.…”
Section: Discussionsupporting
confidence: 84%
“…Thus we postulate that a possible reason for the increased gain in the PF90 condition could be a misinterpretation of the distance to the wall. This hypothesis is in line with recent findings by Ott, Pohl, Halfmann, Hardiess, and Mallot (2016) who found that in order to keep perceived motion constant, participants had to decrease their perceived motion as a hallway narrowed and increase their motion as it widened. However, at the beginning of every trial participants saw a full field view of the hallway, meaning that the participants in all conditions should have had the same mental representation of the hallway and the same understanding of the size of the hallway.…”
Section: The Effect Of Retinal Areasupporting
confidence: 92%
“…Still, speeding on highways does seem to increase as lighting conditions deteriorate (de Bellis et al 2018). Driving speed also varies with the width of a corridor, that is, subjects tend to slow down when passing a constriction and speed up afterward, just as the honey bees shown in figure 4.4d (see, e.g., Ott et al 2016). The implications of these results for the template-matching approach to optic flow analysis have been discussed in section 2.5.3.…”
Section: Beyond Insectsmentioning
confidence: 99%